THE ROLE OF MODIFIED UMEGA MODEL IN PREDICTING E-GOVERNMENT SERVICE ADOPTION IN DEVELOPING COUNTRIES (Contemporary Journal of Social Science Review, 2025)
In developing countries, the implementation of electronic government services is challenging. The Government of Pakistan initiated e-government services in 2002 to modernize the administrative system, as government organizations had previously failed to deliver services effectively. Productivity and performance in government organizations were also low. The main purpose of implementing e-government was to simplify procedures, provide citizens with quick access to services, and ensure accountability among government officials. Although the Government of Pakistan has invested significant financial resources into e-government initiatives, the country remains in the implementation phase. Major barriers to the successful implementation of e-government services include political instability, inefficient bureaucracy, incompetent political leadership, and a lack of policy enforcement. Despite these difficulties, the government launched several e-government projects, largely adopting the model used in Singapore. As a developing country, Pakistan has achieved 15% success in e-government projects, while 49% of projects are considered partially successful. In this research, we investigate the factors that encourage citizens to use e-government services, using a modified UMEGA model-an e-government-specific model designed for developing countries. Performance Expectancy (PE), Perceived Ease of Use (PEOU), ICT Literacy, Perceived Trust (PT), and Perceived Transparency are our independent variables, while Behavioral Intention (BI) to use e-government services is the dependent variable. We also examine the impact of PEOU, ICT Literacy, PE, PT, and Perceived Transparency on citizens' attitudes toward using e-government services. Our findings indicate that PE, PT, Perceived Transparency, and ICT Literacy are important factors that encourage citizens to use e-government services. Additionally, Attitude acts as a mediating variable between the independent variables and the dependent variable. Attitude has a positive impact on PE, PT, Perceived Transparency, and ICT Literacy, further encouraging the use of e-government services among citizens.